Abdominal Panniculectomy: An Analysis of Outcomes in 238 Consecutive Patients over 10 Years. Issue 11 (November 2021) - Kuruoglu, Doga; Salinas, Cristina A.; Tran, Nho V.; Nguyen, Minh-Doan T.; Martinez-Jorge, Jorys; Bite, Uldis; Harless, Christin A.; Sharaf, Basel
Abstract : Background: Panniculectomy is a commonly performed body contouring procedure to address skin laxity and its related complications. This study aimed to assess clinical outcomes of abdominal panniculectomy and identify predictors of complications at a tertiary academic healthcare center. Methods: A retrospective review of patients who underwent panniculectomy between January 2010 and January 2020 at our institution was performed. Exclusion criteria were a history of prior panniculectomy or abdominoplasty. Patient characteristics and clinical outcomes were collected. Univariate and multivariable analyses were performed to assess the risk factors of complications. Results: The mean age in the included 238 patients was 51.7 ± 12.7 years, and the mean body mass index (BMI) at the time of panniculectomy was 33 ± 7.5 kg/m 2 . Median resection weight was 2.7 kg (range: 0.15–14.6) and median length of hospital stay was 2 days (range: 0–24). Mean follow-up time was 50 ± 37 months. The rate of major complications was 22.3%. Revision surgery was performed in 3.4% of the cases. Multivariable analyses demonstrated that increase in BMI ( P = 0.007) and active smoking ( P = 0.026) were significantly associated with increased odds of major complication, and increase in BMI ( P = 0.0004), history of venous thromboembolism ( P = 0.034) and having a concomitant ventral hernia repair ( P = 0.0044) were significantly associated with having a length of hospital stay of 3 days or more. Conclusions: Panniculectomy is generally safe to perform, with major postoperative complication rate of 22.3% in our series. Increase in BMI and active smoking were significantly associated with having a major complication. Higher BMI, concomitant hernia repair, and a history of venous thromboembolism were associated with length of hospital stay of 3 days or more.